Бесконтактный тепловой контроль электронно-вычислительных средств - Panfilova, S. P.; Vlasov, A. I.; Gridnev, V. N.; Chervinsky, A. S. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The article analyzes the applicability of thermography for diagnosing electronic devices. Typical faults detectable by thermal imaging are presented. The advantages of non-contact thermal inspection over contact methods are described, along with specific features of thermography for electronic equipment. The thermographic apparatus is outlined, and recommendations for its selection in electronic diagnostics are provided. An example of applying the thermographic method to check electronic devices is given. The main functions of the software used in thermography and its importance are also described.